2017
DOI: 10.1021/acs.macromol.6b02475
|View full text |Cite
|
Sign up to set email alerts
|

2,2′-Bis(1,3,4-thiadiazole)-Based π-Conjugated Copolymers for Organic Photovoltaics with Exceeding 8% and Its Molecular Weight Dependence of Device Performance

Abstract: A series of novel π-conjugated copolymers based on 2,2′-bis­(1,3,4-thiadiazole) (BTDz) have been developed. Among them, the BTDz-based donor–acceptor alternating copolymer with the (E)-1,2-di­(3-(2-ethyl­hexyl)­thiophene)­vinylene donor unit (PBTDzTV) exhibited a high solubility and high crystallinity. PBTDzTVs favorably self-assembled, forming face-on and edge-on multibilayer structures in thin nanoscale films. The relative volume fractions of these structures varied depending on the polymer’s molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
(90 reference statements)
1
36
0
Order By: Relevance
“…The main absorption peaks of the thin polymers films redshifted and exhibited broader absorption peaks compared to those of the polymers in solution. This occurred because the chains of the thin fluorinated polymers films were likely to have been packed more closely compared to the polymers in solution, thus resulting in aggregation and enhanced intermolecular charge transfer (ICT) …”
Section: Methodsmentioning
confidence: 99%
“…The main absorption peaks of the thin polymers films redshifted and exhibited broader absorption peaks compared to those of the polymers in solution. This occurred because the chains of the thin fluorinated polymers films were likely to have been packed more closely compared to the polymers in solution, thus resulting in aggregation and enhanced intermolecular charge transfer (ICT) …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the M n could be easily affected by synthetic condition such as polymerization time, temperature, concentration, and so on . In recent years, a lot of reported works have demonstrated that the M n usually has great impact on the performance of PSCs via significantly affecting the molecular orientation, hole mobility, domain purity, and vertical composition profiles . However, a systemic study that clarifies the dependence of optimal thickness of active layer on polymer M n , which is of vital importance to develop a facile approach to realize high‐performance thick‐film PSCs, has not been made.…”
Section: Introductionmentioning
confidence: 99%
“…Thiazole derivatives, which contain sulfur and nitrogen atoms, have been considered as electron withdrawing unit candidates for conjugated polymers . Recently, a series of new π‐conjugated donor–acceptor alternating polymers based on various thiazole derivative units was reported; their synthesis and fundamental characterizations were discussed in detail. However, they were investigated in the aspect of only photoelectric performance as an active matrix component in solar cell devices.…”
Section: Molecular Weights and Polydispersity Indices Thermal Propermentioning
confidence: 99%